2022
DOI: 10.48550/arxiv.2201.09068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Massive quiescent galaxies at $z\sim3$: a comparison of selection, stellar population and structural properties with simulation predictions

Abstract: We study stellar population and structural properties of massive log(𝑀 ★ /𝑀 ) > 11 galaxies at 𝑧 ≈ 2.7 in the Magneticum (box 3) and IllustrisTNG (TNG100, TNG300) hydrodynamical simulations. We find stellar mass functions broadly consistent with observations, with no scarcity of massive, quiescent galaxies at 𝑧 ≈ 2.7, but with a higher quiescent galaxy fraction at high masses in IllustrisTNG. Average ages of simulated quiescent galaxies are between ≈ 0.8 and 1.0 Gyr, older by a factor ≈ 2 than observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 140 publications
0
5
0
Order By: Relevance
“…Deep near-infrared photometric surveys of the last decade have suggested larger numbers of massive galaxies at high redshifts than predicted by cosmological galaxy simulations (e.g., Muzzin et al 2013a;Straatman et al 2014;Sherman et al 2019;Marsan et al 2022). More recent simulations have better agreement with observations, but the discrepancy is still a factor of a few to 10 at the highest masses (though see Donnari et al 2021;Lustig et al 2022). In the last several years, spectroscopic confirmation of a handful of galaxies with stellar masses of *  ( ) M M log > 11 and at redshifts of z > 3 have shown that such galaxies do indeed exist in nonnegligible numbers (Marsan et al 2015(Marsan et al , 2017Glazebrook et al 2017;Schreiber et al 2018a;Tanaka et al 2019;Forrest et al 2020aForrest et al , 2020bValentino et al 2020), but a robust measurement of the number density of such galaxies is still lacking.…”
Section: Introductionmentioning
confidence: 85%
“…Deep near-infrared photometric surveys of the last decade have suggested larger numbers of massive galaxies at high redshifts than predicted by cosmological galaxy simulations (e.g., Muzzin et al 2013a;Straatman et al 2014;Sherman et al 2019;Marsan et al 2022). More recent simulations have better agreement with observations, but the discrepancy is still a factor of a few to 10 at the highest masses (though see Donnari et al 2021;Lustig et al 2022). In the last several years, spectroscopic confirmation of a handful of galaxies with stellar masses of *  ( ) M M log > 11 and at redshifts of z > 3 have shown that such galaxies do indeed exist in nonnegligible numbers (Marsan et al 2015(Marsan et al , 2017Glazebrook et al 2017;Schreiber et al 2018a;Tanaka et al 2019;Forrest et al 2020aForrest et al , 2020bValentino et al 2020), but a robust measurement of the number density of such galaxies is still lacking.…”
Section: Introductionmentioning
confidence: 85%
“…Although many studies have been conducted to determine the physical properties and quenching processes of ancient quiescent galaxies (e.g., van Dokkum et al 2015;Park et al 2021;Zhang et al 2022;Lustig et al 2022), TNG provides a means to address a cosmological enigma yet to be resolved in this field, namely the lives and quenching mechanisms of the very first quiescent galaxies in our Universe. The most massive galaxies in the Universe today host maximally old stars (e.g., Thomas et al 2010;McDermid et al 2015), suggesting that they are relics of very early star formation and the early truncation thereof.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in previous studies, the galaxy physics implemented in the Magneticum simulations leads to successfully reproducing basic galaxy properties like the stellar mass-function (Naab & Ostriker 2017;Lustig et al 2022), the environmental impact of galaxy clusters on galaxy properties (Lotz et al 2019) and the appearance of post-starburst galaxies (Lotz et al 2021) as well as the associated AGN population at various redshifts (Hirschmann et al 2014;Steinborn et al 2016;Biffi et al 2018a). At cluster scale, the Magneticum simulations has demonstrated to reproduce the observable X-ray luminosityrelation (Biffi et al 2013), the pressure profile of the ICM (Gupta et al 2017) and the chemical composition (Dolag et al 2017;Biffi et al 2018b) of the ICM, the high concentration observed in fossil groups (Ragagnin et al 2019), as well as the gas properties in between galaxy clusters (Biffi et al 2021).…”
Section: Cosmological Simulations: Magneticummentioning
confidence: 58%